Inner Ear Decompression Sickness (Iedcs) in Divers - Dwi Rahmat; Eka Ari Yuliyani; Muhammad Aulia Hikmah Romadoni (Journal of Social Research, 2022)
Background: Inner ear decompression sickness (IEDCS) is a common disease in divers. In Indonesia, IEDCS is often experienced by diver fishermen in fulfilling their daily needs. In general, decompression sickness (DCS) is caused by the formation of gas bubbles in blood vessels and organ tissues. This is due to the deposition of gas bubbles in the endolymphatic and perilymphatic spaces during the process of their rapid rise to the surface. Objective: This study aims to identify IEDCS disease in divers. Method: This study used a qualitative approach with a case study model that analyzes and identifies the symptoms that appear in divers suffering from IEDCS. Result: Symptoms of classic IEDCS develop in about 30 minutes and are vestibular, these include vertigo, ataxia, nausea, and vomiting. The preferred therapy that can be given to people with DCS and IEDCS is hyperbaric oxygen therapy (recompression therapy) immediately. Complications are rare after hyperbaric oxygen therapy. After therapy and DCS sufferers recover, there will usually still be residual deficits in balance and hearing. Diving according to protocol and providing information about DCS through education, counseling, or other media needs to be done for at-risk groups to create knowledge that is relevant and can take precautions. Conclusion: The disease of decompression of the part ear is common in compressed gas divers. This is due to the deposition of gas bubbles in the endolymphatic and perilymphatic chambers during the process of rising to the surface quickly.